2018
DOI: 10.1113/jp275972
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic stress‐dependent regulation of the mitochondrial biogenic molecular response to high‐intensity exercise in human skeletal muscle

Abstract: The aim of the present study was to examine the impact of exercise-induced metabolic stress on regulation of the molecular responses promoting skeletal muscle mitochondrial biogenesis. Twelve endurance-trained men performed three cycling exercise protocols characterized by different metabolic profiles in a randomized, counter-balanced order. Specifically, two work-matched low-volume supramaximal-intensity intermittent regimes, consisting of repeated-sprint (RS) and speed endurance (SE) exercise, were employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
84
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 89 publications
3
84
1
1
Order By: Relevance
“…For example, a single bout of exercise induces a rapid increase of PGC‐1α protein content in human skeletal muscle (29). Moreover, PGC‐1α translocation to the nucleus (17) and estrogen‐related receptor (ERR)‐α expression occur within 2 h (16). Notably, the initial increase of peroxisome proliferator‐activated receptor‐γ coactivator (PGC)‐1α and ERR‐α transcription appears to induce the expression of MFN2 (16).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a single bout of exercise induces a rapid increase of PGC‐1α protein content in human skeletal muscle (29). Moreover, PGC‐1α translocation to the nucleus (17) and estrogen‐related receptor (ERR)‐α expression occur within 2 h (16). Notably, the initial increase of peroxisome proliferator‐activated receptor‐γ coactivator (PGC)‐1α and ERR‐α transcription appears to induce the expression of MFN2 (16).…”
Section: Discussionmentioning
confidence: 99%
“…Further, Fiorenza et al . () reported that a low‐volume sprint protocol (6 × 20 s ‘all‐out’) elicited increases in gene expression and intracellular signalling that were similar or greater than those elicited by a 50 min bout of moderate‐intensity continuous cycling involving 8 times more work. Other putative signalling events seem to occur above an intensity threshold, such as the fragmentation of the ryanodine receptor 1 protein (RYR1), which was elicited by supramaximal exercise but not lower intensity exercise (Place et al .…”
mentioning
confidence: 97%
“…We are not arguing that lower intensities of exercise are ineffective: prolonged exercise at lower intensities activates mitochondrial biogenesis, albeit perhaps in response to different intracellular signals (Fiorenza et al . ), and increases mitochondrial content (Burgomaster et al . ; Gillen et al .…”
mentioning
confidence: 99%
“…In contrast, given recent data highlighting the role of local metabolic stress in modulating acute exercise‐induced cell signaling pathways (Fiorenza et al. ), we hypothesized that the application of CWI (i.e., a systemic mediated stress) induces negligible regulatory effects on muscles that have already been subjected to the extreme local metabolic challenge of both high‐intensity exercise and low muscle glycogen availability. Confirming our hypothesis, we demonstrate that the application of post‐exercise CWI does not enhance the exercise‐induced expression of PGC‐1α mRNA in muscles that completed an acute high‐intensity cycling protocol with low (i.e., <300 mmol·kg −1 dw) or very low (i.e., <150 mmol·kg −1 dw) pre‐exercise muscle glycogen concentrations.…”
Section: Discussionmentioning
confidence: 94%
“…However, given recent data highlighting the role of local muscle metabolic stress in modulating acute exercise‐induced cell signaling pathways (Fiorenza et al. ), it is suggested that the application of CWI (i.e., a systemic mediated stress) induces negligible regulatory effects on a muscle that has already been subjected to the extreme local metabolic challenge of both high‐intensity exercise and low muscle glycogen availability.…”
Section: Introductionmentioning
confidence: 99%